2020
DOI: 10.1108/jfra-09-2018-0074
|View full text |Cite
|
Sign up to set email alerts
|

The impact of changes in cash flow statement items on audit fees: evidence from Iran

Abstract: Purpose The purpose of this study is to determine whether the incremental difference between the actual level of cash from the optimal amount (excess and insufficient cash) to the abnormal amount of cash (abnormal positive and negative changes in cash) leads to an increase in audit fees. Design/methodology/approach To investigate the main purpose of this study, first, the authors, respectively, estimate the optimal cash flow and the normal (optimal) changes in cash by Oler and Picconi (2014) and Bates, Kahle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 76 publications
0
7
0
1
Order By: Relevance
“…Charl et al (2013) audit fees are sticky, as they do not immediately or thoroughly adjust to changes in their determinants. Salehi et al (2020) argue that ICE will likely mitigate audit risk by improving organisational operations. According to these arguments, we expect that more efficient ICCs within a company, which has resulted in lower agency problems between agent and principal, may result in less audit risk and, subsequently, sticky behaviour of audit fees.…”
Section: Intellectual Capital Components and Audit Fees Stickinessmentioning
confidence: 99%
“…Charl et al (2013) audit fees are sticky, as they do not immediately or thoroughly adjust to changes in their determinants. Salehi et al (2020) argue that ICE will likely mitigate audit risk by improving organisational operations. According to these arguments, we expect that more efficient ICCs within a company, which has resulted in lower agency problems between agent and principal, may result in less audit risk and, subsequently, sticky behaviour of audit fees.…”
Section: Intellectual Capital Components and Audit Fees Stickinessmentioning
confidence: 99%
“…Audit committee formation has been a prerequisite of regulations in developed and developing countries, thus attracting scholarly efforts to investigate regarding its establishment, attributes and activities (McMullen, 1996; Zhou et al , 2018; Salehi et al , 2020). For example, some of the topics assessed in previous research include voluntary formation of audit committees (Pincus et al , 1989; Bradbury, 1990), activities of audit committees (Collier and Gregory, 1999), auditor support and audit committee composition (DeZoort et al , 2003), independence of audit committees (Klein, 2002) and audit committee financial expertise (Krishnan, 2005; Salleh et al , 2017; Zalata et al , 2018).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…They found CFOs powerful in predicting future cash flows than earning and traditional measures. Salehi et al (2018) studied the effect of cash flow statements on audit fees on the companies listed on the Tehran Stock Exchange and found that excess cash holdings reduce the audit fees. Amuzu (2010) studied individual data points from 2003 to 2005 for listed Ghanaian companies.…”
Section: Introductionmentioning
confidence: 99%